2006
DOI: 10.1099/jmm.0.46460-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Campylobacter jejuni using seven single-nucleotide polymorphisms in combination with flaA short variable region sequencing

Abstract: This investigation describes the development of a generally applicable, bioinformatics-driven, single-nucleotide polymorphism (SNP) genotyping assay for the common bacterial gastrointestinal pathogen Campylobacter jejuni. SNPs were identified in silico using the program 'Minimum SNPs', which selects for polymorphisms providing the greatest resolution of bacterial populations based on Simpson's index of diversity (D). The high-D SNPs identified in this study were derived from the combined C. jejuni/Campylobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…However, among the flaA SVR types represented by two or more isolates, 10% of the isolates were discordant with respect to the CC, suggesting that the flaA SVR type does not consistently correlate with the chromosomal genotype. Other studies have also suggested that flaA SVR typing alone is poorly suited for investigation of the molecular epidemiology of C. jejuni isolates (8,9,11,12,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, among the flaA SVR types represented by two or more isolates, 10% of the isolates were discordant with respect to the CC, suggesting that the flaA SVR type does not consistently correlate with the chromosomal genotype. Other studies have also suggested that flaA SVR typing alone is poorly suited for investigation of the molecular epidemiology of C. jejuni isolates (8,9,11,12,35).…”
Section: Discussionmentioning
confidence: 99%
“…The flagellin gene has been a well-accepted marker for Campylobacter genotyping for over 2 decades (4,16,18,19,22,25,32). In this study we have developed a genotyping method based on flaA interrogation using HRM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates included in this study have been subjected to typing based on variation in resolution-optimized MLST database-derived SNPs and resolution-optimized binary markers (17) as well as to the methods addressed in the present study. The SNP-, binary marker-, and HRM-based methods can all be performed on the real-time PCR platform, and they all yield digitizable results (17,(23)(24)(25), thus providing a readily accessible choice of methods or combinations of methods that can be adapted to different tasks and questions. It has previously been shown that the resolution-optimized SNP-defined genotypes correlate well with the MLST-defined population structure; i.e., there was a strong tendency for isolates with identical SNP types to have identical or very similar MLSTs (25).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of more variable targets, such as flagellin-encoding genes, increases the discriminatory power of sequence-based typing. The most frequently used gene for this purpose is flaA (2,5,7,17,20,26,29), although flaB is also used, and as a more stable gene, flaB might become more important (21). Other important factors to consider are the time and effort needed to perform the appropriate data analysis, especially in the context of internationally standardized approaches and the use of publicly available typing tools, such as http://pubmlst.org.…”
mentioning
confidence: 99%